2020
DOI: 10.1523/jneurosci.2462-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Dependent Synaptic Uptake and Cognitive Decline after Stroke and Reperfusion Therapy

Abstract: Despite the success of reperfusion therapy in significantly reducing the extent of infarct expansion after stroke, the effect of revascularization on poststroke neuroinflammation and the role of anti-inflammatory strategies in postreperfusion era are yet to be explored. Here, we investigate whether the neuroinflammatory response may still contribute to neurologic deficits after reperfused stroke by using targeted complement inhibition to suppress poststroke neuroinflammation in mice with or without concurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“… 17 , 19 , 20 More recently, pharmacological inhibition of the complement cascade, including when administered within 24 h after stroke, has been shown to reduce infarct size and promote behavioral recovery. 18 , 21 23 These studies suggest that targeting complement proteins could be a potential neuroprotective strategy after stroke.…”
Section: Resultsmentioning
confidence: 95%
“… 17 , 19 , 20 More recently, pharmacological inhibition of the complement cascade, including when administered within 24 h after stroke, has been shown to reduce infarct size and promote behavioral recovery. 18 , 21 23 These studies suggest that targeting complement proteins could be a potential neuroprotective strategy after stroke.…”
Section: Resultsmentioning
confidence: 95%
“…CNS synthesis of complement components is induced and maintained for extended periods of time in animal models of stroke ( Huang et al, 1999 ; Pavlovski et al, 2012 ) and traumatic brain injury ( Bellander et al, 2001 ). In extensive analyses of the different sequelae in an occlusion model of stroke—acute, subacute, and long-term—Tomlinson and colleagues have demonstrated that a fusion molecule consisting of a single-chain monoclonal antibody directed toward a stroke-induced modified annexin IV linked to the murine CR1 ortholog Cr1-related protein Y prevented opsonic C3b/iC3b deposition on neurons and prevented synaptic uptake ( Alawieh et al, 2020 ) and neuronal phagocytosis by microglia ( Alawieh et al, 2018a ). In addition, the inhibition of complement prevented microglial activation, perhaps because of reduced generation of C5a, which otherwise persisted chronically in this model.…”
Section: Therapeutic Complement Inhibitionmentioning
confidence: 99%
“…The procedure can only be used in ischemic stroke patients with a proximal large artery occlusion, and many hospitals and stroke centers do not have the capability to perform the procedure. In addition, reperfusion therapy does not appear to prevent a subsequent neuroinflammatory response after stroke, and while successful reperfusion can improve motor function outcome, it does not appear to prevent cognitive decline ( 35 ). Thus, there remains an interest in developing neuroprotective strategies to treat stroke, even though very few neuroprotective agents have been shown to be unequivocally beneficial in randomized controlled clinical trials ( 36 , 37 ).…”
Section: Strokementioning
confidence: 99%